Ready-to-eat foods : microbial concerns and control measures - Huang, Lihan; Hwang, Andy (CRC Press, 2010)
Comprehensively reviews individual common RTE food and their specific safety-related aspects since RTE foods are normally consumed without prior cooking, a step that kills pathogenic microorganisms that may be present in the food products.